Risk of Stroke in Systemic Necrotizing Vasculitis: A Nationwide Study Using the National Claims Database - Ahn, Sung Soo; Han, Minkyung; Yoo, Juyoung; Park, Yong-Beom; Jung, Inkyung; Lee, Sang-Won (Frontiers in Immunology, 2021)
Objective: Evidences indicate that the risk of stroke is increased in autoimmune rheumatic diseases. This study aimed investigate the incidence of stroke in patients with systemic necrotizing vasculitis (SNV) using the national health database. Methods: Data were obtained from the Korean National Claims database between 2010 and 2018 to identify incident SNV [anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV) and polyarteritis nodosa (PAN)] cases. The standardized incidence ratio (SIR) and incidence rate ratio (IRR) were calculated to estimate the risk of stroke in patients with SNV compared to the general population and among disease subgroups. Time-dependent Cox’s regression analysis was performed to identify risk factors for stroke. Results: Among 2644 incident SNV cases, 159 patients (6.0%) were affected by stroke. The overall risk of stroke was significantly higher in patients with SNV compared to the general population (SIR 8.42). Stroke event rates were the highest within the first year of SNV diagnosis (67.3%). Among disease subgroups, patients with microscopic polyangiitis (MPA) exhibited higher IRR compared to PAN (adjusted IRR 1.98). In Cox’s hazard analysis, older age and MPA were associated with higher risk of stroke [hazard ratio (HR) 1.05 and 1.88], whereas the administration of cyclophosphamide, azathioprine/mizoribine, methotrexate, and statins were protective in stroke (HR 0.26, 0.34, 0.49, and 0.50, respectively). Conclusion: A considerable number of SNV patients experienced stroke, especially in the early phase of disease. Older age and MPA diagnosis were associated with elevated risk of stroke, while the administration of immunosuppressive agents and statins was beneficial in preventing stroke.